Comparing the Decision-making Rights of Adults with Declining Cognitive Abilities with Those of Children - Charlotte Mol; Fiore Schuthof (Utrecht Law Review, 2024)
Both adults with declining cognitive abilities (DCA) and children may experience limits in their decision-making capacity. Yet whereas this decision-making capacity increases for children as they age and mature, it gradually decreases in the case of adults with DCA. The Convention on the Rights of the Child (CRC) and the Convention on the Rights of Persons with Disabilities (CRPD) contain several decision-making rights and principles that are relevant for these groups. This article compares these decision-making rights and principles by addressing four key aspects in decision-making: the decision-maker, the types of decisions, the right to participation versus the right to support in the exercise of legal capacity, and the best interests principle. Through the comparison and the visualisation of a conceptual model, insights and lessons for both children and adults with DCA are sought.